Penetrating brain injury with hypopituitarism - Rachel D. Appelbaum; Kristina E. Neri; Kristin A. Rebo; Samuel P. Carmichael, II (Trauma Case Reports, 2022)
A 34-year-old healthy male presented as a trauma activation after sustaining a gunshot wound to his face. CT head imaging was suggestive of a ballistic fragment adjacent to a posterior wall sphenoid sinus fracture with likely a small volume of adjacent blood products. He was ultimately diagnosed with hypopituitarism which included central diabetes insipidus, central hypothyroid, and adrenocorticotropic hormone deficiency secondary to cortisol deficiency. This case illustrates the spectrum of endocrine dysfunction that can occur with skull base injuries, and the appropriate pituitary-function screening and treatment that should be performed if there is clinical concern. Early recognition and prompt treatment of pituitary insufficiency can facilitate overall rehabilitation after TBI.